Enhancing shape-recovery ratio of 4D printed polylactic acid (PLA) structures through processing parameter optimization - Saptaji, Kushendarsyah; Rochmad, Camytha Octanuryati; Juniasih, Octarina Adiati; Sunnardianto, Gagus Ketut; Triawan, Farid; Anwar Ilmar, Ramadhan; Azmir, Azhari (Springer Science and Business Media Deutschland GmbH, 2024)
The utilization of shape memory polymers (SMP) is expanding across various industries due to their unique behavior. The shape memory polymers, such as, polylactic acid (PLA) can be fabricated as shape transforming structure using 3D printing and make use of thermal stimulation which also designated as four-dimensional (4D) printing process. One crucial aspect of these materials is the recovery process of the shape-transforming structure after the load is released. This recovery process plays a vital role in determining the behavior of the materials. The infuence of 3D printing parameters and the establishment of recovery properties of the material and the correlations between the memory properties and thermal recovery have not been extensively explored. Therefore, this study aims to examine the activation of 3D printing polylactic acid (PLA) shape memory polymer (SMP) and the efects of varying parameters when exposed to thermal stimulation. The PLA specimens were printed in the semicircular shape and the parameters namely thickness, infll density, printing speed, deformation temperature, and recovery temperature are varied to obtain diferent shape-recovery ratio. The experimental results indicated that the highest recovery ratio observed was 0.784. This was achieved with the following combination of parameters: a thickness of 3 mm, an infll density of 50%, a printing speed of 30 mm/s, a deformation temperature of 55 °C, and a recovery temperature of 80 °C. Furthermore, ANOVA analysis was performed to obtain the pivotal constituent of the data and the contribution of every experimental factor. It denoted that the thickness parameter was the signifcant factor. The experimental results recorded that the PLA structures had the optimum shape memory properties with combination of high recovery temperature, faster printing speed, lower density, and thinner component.